Employee value proposition as a human resource management strategy among Philippines SMEs in preparation for ASEAN integration - Binghay, Virgel C. (2015)
The planned ASEAN integration becomes more and more inevitable. The full implementation of the ASEAN Economic Community, in particular, will bring about the free flow of skilled labor, among others, to its member countries. The entire Philippines, as part of the ASEAN, should gear up for this transition. This includes the country's small and medium enterprises (SMEs), an important driver of economic growth and source of employment. However, challenges still remain in developing Philippine SMEs. Specifically, human resource management in this sector remains poor and lacking. With the influx of labor from neighboring countries, diversity in the workforce is to be expected. Thus, good people management becomes even more crucial in ensuring the competitive advantage of our SMEs. Employee value proposition is viewed as an important strategy to improve the quality of human resource management in the country and provide an edge for our SMEs in the face of the changes ahead.
Keywords: Personnel management; Small business; Association of Southeast Asian Nations